2008
DOI: 10.1074/jbc.m803754200
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Effects of Insulin-like Growth Factor-I on Growth Plate Chondrogenesis Are Mediated by Nuclear Factor-κB p65

Abstract: Insulin-like growth factor-I (IGF-I) is an important regulator of endochondral ossification. However, little is known about the signaling pathways activated by IGF-I in growth plate chondrocytes. We have previously shown that NF-B-p65 facilitates growth plate chondrogenesis. In this study, we first cultured rat metatarsal bones with IGF-I and/or pyrrolidine dithiocarbamate (PDTC), a known NF-B inhibitor. The IGF-I-mediated stimulation of metatarsal growth and growth plate chondrogenesis was neutralized by PDTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 46 publications
4
45
0
Order By: Relevance
“…The targeted silencing of NF-B p65 expression or activity prevented the GH stimulation of IGF-1 mRNA and protein expression, suggesting that both Stat5b and NF-B p65 are necessary to mediate the GH stimulatory effects on IGF-1 in chondrocytes. Interestingly, we have previously shown that NF-B p65 mediates the stimulatory effects of IGF-1 on chondrocyte proliferation and differentia- tion and demonstrated its preventive effects on chondrocyte apoptosis (8). Thus, our study supports a reciprocal functional interaction between NF-B p65 and IGF-1 in which the transcription factor modulates both IGF-1 synthesis and action in growth plate chondrocytes.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The targeted silencing of NF-B p65 expression or activity prevented the GH stimulation of IGF-1 mRNA and protein expression, suggesting that both Stat5b and NF-B p65 are necessary to mediate the GH stimulatory effects on IGF-1 in chondrocytes. Interestingly, we have previously shown that NF-B p65 mediates the stimulatory effects of IGF-1 on chondrocyte proliferation and differentia- tion and demonstrated its preventive effects on chondrocyte apoptosis (8). Thus, our study supports a reciprocal functional interaction between NF-B p65 and IGF-1 in which the transcription factor modulates both IGF-1 synthesis and action in growth plate chondrocytes.…”
Section: Discussionsupporting
confidence: 68%
“…Whole Metatarsal Culture-The second, third, and fourth metatarsal bone rudiments were isolated from Sprague-Dawley rat embryos (20 days postcoitum) and cultured individually in 24-well plates (8). Each well contained 0.5 ml of minimum essential medium (Invitrogen) supplemented with 0.05 mg/ml ascorbic acid (Invitrogen), 1 mM sodium glycerophosphate (Sigma-Aldrich), 0.2% bovine serum albumin (Sigma), 100 units/ml penicillin, and 100 g/ml streptomycin (Invitrogen) without or with 10 ng/ml recombinant mouse GH and/or 1 M PDTC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, BMP2 also drives terminal differentiation, supporting the expression of collagen X. NF-κB mediates the regulation of growth plate chondrogenesis by IGF-1, which stimulates longitudinal bone growth by inducing chondrocyte proliferation and maturation and inhibiting apoptosis. The IGF-1 receptor is a receptor tyrosine kinase that activates an array of intracellular signaling pathways, and recent studies have shown that the major effects of IGF-1 on the growth plate appear to be mediated by p65 [54,55]. Chemical inhibition of NF-κB blocks the stimulatory effects of IGF-1 on chondrocyte proliferation and hypertrophy in rat metatarsal explant cultures and its inhibitory effect on apoptosis in cultured chondrocytes.…”
Section: Nf-κb In Chondrocytesmentioning
confidence: 99%
“…Other studies have reported that WISP3 interacts with BMP and components of the Wnt1 signaling pathway including LRP6 and Fz8 (Nakamura et al, 2007). In light of the fact that WISP3 harbors a potential IGF1 binding motif and IGF1 is required for cartilage/bone growth (McQuillan et al, 1986;Ohlsson et al, 1992;Wang et al, 1999;Wu et al, 2008), it is important to decipher if WISP3 also physically interacts with IGF1 and controls its mode of actions. Although, WISP3 has been demonstrated to suppress IGF1 signaling in breast cancer as well as chondrocyte cell lines (Kleer et al, 2004;Cui et al, 2007;Lorenzatti et al, 2011), WISP3-IGF1 interaction and its potential influence on chondrocyte hypertrophy has not been documented.…”
mentioning
confidence: 99%